2022
DOI: 10.1038/s41419-022-05064-5
|View full text |Cite
|
Sign up to set email alerts
|

The crosstalk between endothelial cells and vascular smooth muscle cells aggravates high phosphorus-induced arterial calcification

Abstract: Arterial calcification is highly prevalent, particularly in patients with end-stage renal disease (ESRD). The osteogenic differentiation of vascular smooth muscle cells (VSMCs) is the critical process for the development of arterial calcification. However, the detailed mechanism of VSMCs calcification remains to be elucidated. Here, we investigated the role of exosomes (Exos) derived from endothelial cells (ECs) in arterial calcification and its potential mechanisms in ESRD. Accelerated VSMCs calcification was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…In addition, given their location in the innermost layer of the blood vessel lumen and preferential reception of various pro‐calcifying stimuli, ECs can pass messages to vascular wall cells and communicate with them. Crosstalk between ECs and VSMCs via cytokines through a paracrine mechanism, extracellular vesicles (Freise et al, 2021; X. Lin et al, 2022), MiRNAs and myoendothelial gap junctions also plays a role in VC. Although progress has been made in understanding the multicellular communication during VC, it is still largely assumptive and needs to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, given their location in the innermost layer of the blood vessel lumen and preferential reception of various pro‐calcifying stimuli, ECs can pass messages to vascular wall cells and communicate with them. Crosstalk between ECs and VSMCs via cytokines through a paracrine mechanism, extracellular vesicles (Freise et al, 2021; X. Lin et al, 2022), MiRNAs and myoendothelial gap junctions also plays a role in VC. Although progress has been made in understanding the multicellular communication during VC, it is still largely assumptive and needs to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…[ 15 ] Endothelial cell-derived exosomal miR-670-3p can promote arterial calcification by targeting insulin-like growth factor-1, which may be a potential therapeutic target for arterial calcification in hemodialysis patients. [ 16 ]…”
Section: Introductionmentioning
confidence: 99%
“…[15] Endothelial cell-derived exosomal miR-670-3p can promote arterial calcification by targeting insulin-like growth factor-1, which may be a potential therapeutic target for arterial calcification in hemodialysis patients. [16] There is a close relationship between vascular calcification and osteoporosis in CKD patients. [17] Vascular smooth muscle cells and bone morphogenetic cells are derived from the same mesenchymal stem cell line.…”
Section: Introductionmentioning
confidence: 99%
“…Calci cation of the major arteries is an important phenotype of vascular ageing. Researchers have found that exosomes play different roles in MAC [20][21][22]. Exosomes may serve as communication vesicles and mediate vascular calci cation at ambient temperature.…”
Section: Introductionmentioning
confidence: 99%